PENGARUH KONSUMSI BAWANG BATAK TERHADAP KEPUTIHAN PADA WANITA USIA SUBUR DI DESA LAU RAKIT KECAMATAN STM HILIR KABUPATEN DELI SERDANG - Novita Br Ginting Munthe; Iskandar Markus Sembiring; Wilda Wahyuni Siregar (JURNAL KEBIDANAN KESTRA (JKK), 2019)
The health of female sex organs is something that needs special attention, especially in maintaining cleanliness at this time. In the vagina there is normal flora (microorganisms) which must be balanced. If this can not be done by women, it will cause disorders such as vaginal discharge. One well-known genus of plants that is widely used by the community is Batak (Allium). Most of this genus is used by the community as a spice in cooking and traditional medicine. Batak onion plants can inhibit the growth of microorganisms such as fungi that cause vaginal discharge. This study aims to determine the effect of the onion batak on Fertile Age Women (WUS) who experience vaginal discharge in Lau Rakit Village, STM Hilir District, Deli Serdang Regency, North Sumatra Province. The research method uses a "quasy experiment" research design with a "pretest-posttest with control group" design. The population in this study were all WUS in Lau Rakit Village, STM Hilir Sub-District, Deli Serdang Regency, North Sumatra Province. Sampling was done by random sampling using cluster sampling technique. A total of 36 samples were taken by cluster sampling from the entire population in Hamlet (I, II, III) Lau Rakit Village, Sub-District STM Hilir, Deli Serdang Regency, North Sumatra Province, which consisted of 18 respondents as an experimental group and 18 respondents as a control group. Research instruments using questionnaires and data analysis using the Wilcoxon test and the Mann Whitney test. The results showed that these onion plants can inhibit the growth of microorganisms such as fungi that cause vaginal discharge. From the results of this study it is expected that women who experience vaginal discharge can apply the Batak onion plant as a non-pharmacological drug and make the Batak onion plant a family medicinal plant.